2001
DOI: 10.1017/s0376892901000169
|View full text |Cite
|
Sign up to set email alerts
|

Local attitudes towards conservation and tourism around Komodo National Park, Indonesia

Abstract: Ensuring local support for protected areas is increasingly viewed as an important element of biodiversity conservation. This is often predicated on the provision of benefits from protected areas, and a common means of providing such benefits is tourism development. However, the relationship between receipt of tourism benefits and support for conservation has not been explored. This study examined local attitudes towards protected area tourism and the effects of tourism benefits on local support for Komodo Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
3
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(206 citation statements)
references
References 20 publications
12
181
3
10
Order By: Relevance
“…If the planned tourism schemes come to fruition, community members' attitudes toward predators should improve. However, previous work has shown that when people do not receive expected benefits, their attitudes may ultimately become worse (Western, 1994;Walpole and Goodwin, 2001;Walpole and Thouless, 2005). Although we found that community members' tolerance for wild dogs was greater if some of their household income came from tourism, we found no increased tolerance for predators if benefits were shared among the community as a whole (e.g., schools built).…”
Section: Options To Promote Coexistence Between People and Predatorscontrasting
confidence: 79%
See 1 more Smart Citation
“…If the planned tourism schemes come to fruition, community members' attitudes toward predators should improve. However, previous work has shown that when people do not receive expected benefits, their attitudes may ultimately become worse (Western, 1994;Walpole and Goodwin, 2001;Walpole and Thouless, 2005). Although we found that community members' tolerance for wild dogs was greater if some of their household income came from tourism, we found no increased tolerance for predators if benefits were shared among the community as a whole (e.g., schools built).…”
Section: Options To Promote Coexistence Between People and Predatorscontrasting
confidence: 79%
“…Although we found that community members' tolerance for wild dogs was greater if some of their household income came from tourism, we found no increased tolerance for predators if benefits were shared among the community as a whole (e.g., schools built). This finding is in keeping with the increasing realization that if benefitsharing schemes are to succeed, benefits must reach individuals (Walpole and Goodwin, 2001;Walpole and Thouless, 2005).…”
Section: Options To Promote Coexistence Between People and Predatorssupporting
confidence: 75%
“…This is due to inadequate local residents' environmental knowledge to realize the impacts of tourism [30, p.58]. Although the environmental impacts of tourism development might have been justified by employment and individual economic gains [29,30,36], but these benefits can only continue if the quality of the environment is not threatened. Local people should learn to use their assets but not to use them up.…”
Section: Increasing Local People Awarenessmentioning
confidence: 99%
“…Negative attitudes are frequently associated with situations where the perceived costs to individuals and communities outweigh the perceived benefits [20][21][22]. One of the most frequently discussed factors influencing local people's acceptance of protected areas is place attachment (reviewed e.g., in [23]).…”
Section: Introductionmentioning
confidence: 99%